Textbook of Critical Care: Including Trauma and Emergency Care - Mehta, Y. Yatin; Sharma, J. Jeetendra; Mehta, C. Chitra (Jaypee Brothers Medical Publishers, 2022)
Critical care has been growing at a rapid pace all over the world, including underdeveloped and developing countries. Critical Care is one of the most important medical specialties as it deals with critically ill patients who are at a risk of, or are recovering from conditions that may be life threatening. This book is divided to 14 sections and composed of total 124 chapters. Section 1 deals with general principles of critical care, including severity scoring, and monitoring various aspects of ventilation, extracorporeal membrane oxygenation (ECMO), sugar control, sedoanalgesia, delirium, etc. Section 2 deals with all aspects of acute cardiovascular pathology requiring ICU admission. Section 3 presents critical care in cases of acute respiratory syndrome, respiratory failure, obstructive pulmonary diseases, etc. Section 4 is on acute kidney infection and renal replacement therapy. Section 5 also contains chapters on how to approach elevated live enzymes and portal hypertension, along with the common ICU issues related to gastrointestinal (GI), pancreas and liver. Section 6, 7 and 8 covers a brief discussion on neurology, endocrine and post-surgical critical care. Obstetric critical care, and hematology, rheumatology and oncology are poorly recognized and poorly developed field in the underdeveloped and developing countries, so section 9 and 10 have special significance in the book. Section 11 deals with bacterial, viral, fungal, rickettsial infections, including community-acquired and nosocomial. Section 12 contains chapters on poisoning, snakebites and environmental injuries needing critical care. Section 13 deals separately with initial assessment followed by head, chest, spine, long bones and abdominal trauma with their complications. Last but not the least is the potpourri which includes brain death, end of life, ICU design and research. These are covered in Section 14.